THREE THINGS WE LEARNED ABOUT VR - Arulselvi, Uthayakumaran; Umi Kalsom, Masrom; Wan Jumani, Fauzi; Wan Noor Farah, Wan Shamsuddin; Rosjuliana Hidayu, Rosli; Nur Syafawati, Sabuan (Pusat Bahasa Moden (PBM), 2024)
15 February 2024 - In an attempt to investigate the living and breathing landscape of Virtual Reality (VR) technology, six academic members of the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah embarked on a benchmarking session that led and transported them through the dynamic universe of VAR LIVE, an innovative virtual reality theme park and into the sophistication of Virtual Online Future Technology and Extended Reality (VORTEX XR) Lab at Taylor’s University.